HPV testing in cervical cancer formalin-fixed paraffin embedded tissues: Reliability of the Xpert HPV test and high-risk HPV genotypes distribution in Tunisia - Yasmine Ben Taher; Mariem Ben Rekaya; Emna Romdhane; Baligh Miladi; Linda Bel Hadj Kacem; Ahmed Med H’mayada; Nadia Ben Mansour; Farah Sassi; Emna Chelbi; Monia Tangour; Ahlem Blel; Soumaya Rammeh (PLoS ONE, 2025)
Objectives This study aims to assess the performance of the Xpert HPV test for the detection and genotyping of high-risk HPVs (HR-HPV) on FFPE cervical cancer (CC) tissues and to determine the distribution of HR-HPV genotypes in a CC Tunisian series. Methods The Xpert HPV test was conducted on purified DNA from 134 FFPE CC tissues. A single-tube multiplex polymerase chain reaction (PCR) served as a comparator assay to evaluate Xpert HPV performance in detecting and genotyping HR-HPVs. Discordant cases were tested using uniplex PCR. Results The Xpert HPV test generated valid results in 131/134 (97.8%) samples. Sensitivity, specificity, positive and negative predictive values of Xpert HPV for HR-HPV detection among valid samples were 99.16%, 100%, 100%, and 92.31%, respectively. Agreement between Xpert HPV and multiplex PCR for HPV detection was observed in 131/134 cases (97.8%), with a kappa value of 0.892. Agreement between Xpert HPV and Multiplex PCR for HR-HPV genotyping was 96.6%. Combining assays results and after confirmation with uniplex PCR, HR-HPVs were detected in 119/134 (88.8%) samples and 11 HR-HPV genotypes were detected with a predominance of HPV 16 (71%), followed by HPV 31 (8%) and HPV 18 (5%). Conclusion This study demonstrated a high accuracy of the Xpert-HPV test for HR-HPVs detection and genotyping in FFPE CC tissues and revealed a distinct distribution of HR-HPVs in Tunisia.